1989
DOI: 10.1210/endo-125-4-1904
|View full text |Cite
|
Sign up to set email alerts
|

Relative Importance of Newly Synthesized and Stored Hormone to Basal Secretion by Growth Hormone and Prolactin Cells*

Abstract: It is generally accepted that under basal conditions there is preferential release of newly synthesized hormone by a number of endocrine cell type, including those that secrete GH or PRL. However, the cellular basis for this phenomenon along with the relative contribution of stored hormone to basal secretion has yet to be clearly established. In the present study, we employed reverse hemolytic plaque assays to monitor basal and stimulated release of GH and PRL from individual cells in which de novo protein syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This has made it possible to segregate LDCVs into different subpopulations according to their age. We have shown that newly synthesized LDCVs are located in peripheral areas, from which they are preferentially released by nicotine, which explains previous reports that newly synthesized peptides are secreted quickly [13,14]. The swift translocation of newly synthesized LDCVs from the Golgi to the cell membrane agrees with a recent analysis of vesicle dynamics in PC12 cells [15].…”
Section: Discussionsupporting
confidence: 90%
“…This has made it possible to segregate LDCVs into different subpopulations according to their age. We have shown that newly synthesized LDCVs are located in peripheral areas, from which they are preferentially released by nicotine, which explains previous reports that newly synthesized peptides are secreted quickly [13,14]. The swift translocation of newly synthesized LDCVs from the Golgi to the cell membrane agrees with a recent analysis of vesicle dynamics in PC12 cells [15].…”
Section: Discussionsupporting
confidence: 90%
“…To evaluate the role of protein synthesis on CM-induced stimulation of PRL release, male pituitary fragments were incubated in control Earle’s medium or in CM, either with or without 50 µg/ml CHx, a specific inhibitor of RNA protein translation that has been employed previously for inhibiting PRL synthesis [24, 25]. As shown in figure 8, basal PRL secretion (about 1.8 µg/mg tissue) was not affected by the presence of CHx in the medium.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the participation of protein synthesis on CM-induced stimulation of PRL release from male pituitary fragments, the inhibitor CHx [24, 25] was used (50 µg/ml; Sigma). Similarly, to examine the role of vesicle trafficking to the plasma membrane, a mixture of inhibitors was used (50 µ M colchicine, 5 µ M vincristine and 20 µ M cytochalasin D; Sigma) [26,27,28,29].…”
Section: Methodsmentioning
confidence: 99%
“…Newly synthesized hormones in endocrine cells, including PRL in pituitary cells, can be preferentially released (Walker and Farquhar, 1980;Gold et al, 1982;Rhodes and Halban, 1987;Chen at al., 1989). It may be possible that newly synthesized hormone merged with the recycling granules in an intermediate compartment such as immature granules or the endosomal recycling compartment..…”
Section: Preferential Use Of Recycling Granulesmentioning
confidence: 99%